Nonlinear Viscoelastic Response of Thermoplastic-Elastomer Melts (Advances in Applied Mathematics and Mechanics, 2010)
Observations are reported on thermoplastic elastomer (ethylene-octene copolymer) melt in small-amplitude shear oscillatory tests and start-up shear testswith various strain rates in the interval of temperaturesbetween 120 and 210 $^{°}$C. Based on the concept of heterogeneous non-affine polymer networks,constitutive equations are developed for the thermo-mechanicalbehavior of a melt at three-dimensional deformations withfinite strains. Adjustable parameters in the stress-strain relationsare found by fitting the experimental data.The model is applied to the analysis of Poiseuille flow.The effects of temperature and pressure gradient on the steadyvelocity profile are studied numerically.